Uji Efektivitas Ekstrak Etanol Ikan Gabus (Channa striata) Terhadap Penurunan Kadar Glukosa Darah Mencit Jantan (Mus musculus) - Muhammad Gunawan; Safriana Safriana; Andilala Andilala (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Cork fish can help speed up the healing process of diabetes. Diabetes mellitus is a metabolic disease characterized by symptoms of hyperglycemia as a result of impaired insulin secretion and/or increased cell resistance to insulin. The purpose of this study was to determine the ethanol extract of Cork fish (Channa striata) has the most effective effect in lowering blood glucose levels. Methods: experimental research that begins with extracting the meat and skin of the Cork fish by means of percolation, the solvent used is 70% ethanol, the results obtained are ethanol extract of the Cork fish. Tests for decreasing blood glucose levels of mice using 30 mice and divided into 6 groups. Group I (solvent control) Na CMC 0.5%, group II (comparator/glibenclamide), group III (comparison/herbal medicine), group IV, V and VI (treatment of Cork fish ethanol extract dose 0.45; 0.0, 9 and 1.8 g/KgBB). Blood sugar levels of each group were statistically analyzed using the One Way ANOVA method and Duncan's Post-Hoc test using SPSS. Statistical test results for blood glucose levels between the glibenclamide, herbal medicine and ethanol extract of Cork fish showed a significant difference with an α value > 0.05. From the results of the study it can be concluded that the ethanol extract of Cork fish has glucose-induced blood glucose lowering activity in mice with an effective dose of 1.8 g/kgBB.